2010
DOI: 10.3382/ps.2009-00280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary α-tocopherol, selenium, and their different combinations on growth performance and meat quality of broiler chickens

Abstract: This study investigated the effect of different levels of dietary supplementation with alpha-tocopherol or Se, or both, on growth performance and meat quality of broiler chickens. A total of 270 broiler chickens were assigned to 6 dietary treatments (0, 50, 100, or 200 IU of supplemental alpha-tocopherol; 0.3 ppm supplemental Se; or 100 IU of alpha-tocopherol plus 0.3 ppm Se) with 3 replicates of 15 chickens per pen. Growth performance was recorded at 1 and 35 d. At the end of this experiment, 10 broilers per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 22 publications
4
20
3
3
Order By: Relevance
“…In the group with additional supplementation of both vitamin E and Se, FCR was also significantly worse than in the remaining groups. These findings are in opposition to those of many authors, who reported that the modification of the dietary n-6/n-3 PUFA ratio with the use of plant oils and/or supplementation of diets with higher levels of vitamin E or vitamin E and Se is usually without consequences (Cortinas et al, 2004;Kim et al, 2010;Qi et al, 2010) or has positive effects on bird performance (Młodkowski et al, 2003;Koreleski and Świątkiewicz, 2006).…”
Section: Discussioncontrasting
confidence: 94%
“…In the group with additional supplementation of both vitamin E and Se, FCR was also significantly worse than in the remaining groups. These findings are in opposition to those of many authors, who reported that the modification of the dietary n-6/n-3 PUFA ratio with the use of plant oils and/or supplementation of diets with higher levels of vitamin E or vitamin E and Se is usually without consequences (Cortinas et al, 2004;Kim et al, 2010;Qi et al, 2010) or has positive effects on bird performance (Młodkowski et al, 2003;Koreleski and Świątkiewicz, 2006).…”
Section: Discussioncontrasting
confidence: 94%
“…With the aim of removing free radicals, antioxidants are added to the feed [10,17,20,27,34,45]. In the present study, vitamin E and selenium supplementation had no effect on lipid oxidation of the breast meat under TN condition, which is not consistent with the results of previous studies [6,16,22,26,45,47,49].…”
Section: Discussioncontrasting
confidence: 77%
“…Moreover, in some studies, the concentrations of MDA in the meat have been reported per milligram protein [47]. It is also well known that the rate of MDA production in the meat is highly affected by storage time and storage temperature [22,26]. However, according to the range provided by Coetzee and Hoffman [9] for MDA content, all meat samples examined in the present study can be considered as good quality.…”
Section: Discussionmentioning
confidence: 76%
“…Selenium (Se) is an essential trace element that is required for the activity of selenoproteins involved in antioxidant defence, thyroid hormone deiodination, and other vital physiological functions (Surai, 2006). Several authors have studied the effect of a combination of Se and vitamin E on the antioxidative system in broiler chickens (Surai, 2000;Skřivan et al, 2008;Kim et al, 2010) and laying hens (Skřivan et al, 2010). Skřivan et al (2012) investigated the combined effect of dietary vitamin C and Se on the composition and oxidative stability of the meat of broiler chickens.…”
mentioning
confidence: 99%